STUDY OF THE EFFECT OF NEAR FAULT RUPTURE DIRECTIVITY ON SPECTRA RESPONSE AT SOIL SURFACE AND STRUCTURE DESIGN OF INTEGRAL BRIDGE (CASE STUDY: PALU BRIDGE 4 CENTRAL SULAWESI PROVINCE) - Febriant, Mohammad
Bridge construction is generally designed to avoid active fault lines. However, avoiding this is becoming increasingly difficult due to Indonesia having 295 active fault points based on the 2017 Earthquake Map. Active faults pose a higher earthquake risk due to spatial movements, which can potentially damage structures, including permanent tectonic shifts along fault lines. Detailed regulations for earthquake loads caused by active faults have not been specified in SNI 2833:2016. The impact of active faults on bridge design has not been widely studied. This study examines the effect of active faults in terms of generating spectral responses on the surface and their influence on the design of integral bridge structures. The ground-level spectral response is generated by conducting a site-specific response analysis to thoroughly investigate the impact of earthquakes caused by active faults on the structural response. In creating the spectral response, a directivity effect is caused by the propagation of earthquake waves due to active faults. This effect results in an increased spectral acceleration for earthquake waves traveling perpendicular to the fault plane. Ground movements caused by active faults exhibit pulse characteristics in their earthquake waves. When an earthquake wave with a pulse effect occurs, there is a sudden surge of energy and high intensity in a very short time. This study was conducted on Palu Bridge 4, an integral concrete bridge structure with a main span of 116 m and two side spans of 66.7 m each. The bridge is situated near the Palu Koro Fault. The study examines the effects of earthquake waves resulting from the movement of the Palu Koro Fault on the response spectra at ground level using the site-specific response analysis method and its impact on the design of Palu Bridge 4, considering both linear and nonlinear analyses. Sitespecific response analysis was carried out while accounting for the occurring directivity effect. Evaluation of the bridge structure from a linear perspective includes spectral response analysis, encompassing the examination of the column interaction diagram on the pier, as well as its shear force. Nonlinear analysis, specifically Non- Linear Time History Analysis, is conducted, considering ground motion containing pulse effects. The results are then further evaluated against the bridge performance level criteria outlined in NCHRP 440 and 949 documents. The findings of this study indicate that the spectral response at the surface, attributed to the directivity effect, exhibits variations depending on the direction of earthquake wave propagation. The spectral response at the surface, in the direction parallel to the fault plane (Fault Parallel), displays a peak acceleration at a high period and a long peak period. A similar pattern is observed in the surface spectral response for the direction perpendicular to the fault plane (Fault Normal); however, the latter experiences an increase in spectral acceleration at periods above 1 second, ranging from 27% to 39.7%, due to the directivity effect. The outcomes of the spectral response analysis on the Palu Bridge 4 structure reveal that the directivity effect does not significantly impact the bridge's structural response. This is attributed to the fact that the fundamental period of Palu Bridge 4 is 0.515 seconds, while the directivity effect only occurs for periods greater than 1 second. The Non-Linear Time History Analysis results demonstrate that the bridge structure exhibits the highest response in terms of strain and drift during the occurrence of a pulse. Evaluating the bridge's performance against the criteria outlined in NCHRP 440 and 949 documents in terms of drift ratio and strain shows that the Palu Bridge 4 structure remains within fully operational limits following the earthquake event.